Pengaruh Motivasi, Dan Kepuasan Kerja Terhadap Disiplin Kerja Pegawai UPTD Perikanan Air Payau Dan Laut Wilayah Utara Provinsi Jawa Barat - Ari Budiman; Apri Budianto; Enas Enas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The research was conducted with the aim of knowing the effect of motivation and job satisfaction on the work discipline of UPTD employees in brackish water and marine fisheries in the northern region of West Java province. The method used in this research is descriptive design analysis using survey techniques. The results showed that work motivation in the UPTD of brackish water and sea fisheries in the northern region of West Java Province was in the very high category, so that work motivation had a positive and significant effect on employee work discipline. Job satisfaction in the UPTD of brackish water and sea fisheries in the northern region of West Java Province is in the very high category, so that job satisfaction has a positive and significant effect on employee work discipline. Work discipline in the UPTD of brackish water and marine fisheries in the northern region of West Java Province is in the very high category, so that motivation and job satisfaction have a positive and significant effect on employee work discipline.